Bioética e câncer de mama - Andrade Urban, Cicero (Studia Bioethica, 2011)
Bioethics can give important contributions to the medical speciality of Senology. Breast cancer is a complex disease, needing a deeper bioethical helping for some controversies in clinical decisions. The main bioethical questions in Senology like: research involving humans, public health decisions, and clinical decisions, and the care at the end of life were discussed in this paper. There is a cathegoric needing for the Bioethics integration in the postgraduation programs in Senology.